Comparative study of the serum calcium level in normal pregnancy and pre-eclamptic women in a tertiary centre in India - Chaitra Ramachandra; Rekha Rekha; Roopa Roopa; Shankaregowda Shankaregowda; Nirupama Y.S. (International Journal of Medical Research and Review, 2016)
Introduction: Pre-eclampsia is a significant and a common cause of maternal and foetal morbidity and mortality. Role for micronutrients supplementation in preventing preeclampsia is under extensive research. Among these, increasing calcium intake can reduce the risk of pregnancy induced hypertensive disorders.Aim: To compare the level of Serum calcium between the normal pregnancy and preeclampsia patients.Methods and Materials: This prospective double blinded case control study was conducted at Department of Obstetrics and Gynaecology, BGS Global Medical College, Bangalore from January 2015 to December 2015. A total of 120 women attending the antenatal clinic and admitted in the obstetric ward were included in the study. Among the 120 women included, 60 were with pre-eclampsia and the other 60 were normotensive patients. The pre-eclamptic patients were chosen in accordance with the National Institute for Health and Care Excellence (NICE) guidelines on hypertension. Serum calcium was measured by Colorimetric method. Data analysis was done by Graph Pad Instat (Version 3.10).Results: The study included a total of 120 patients with 60 normotensive (Group B) and 60 patients with preeclampsia patients (Group A). Majority of the patients were primigravida in the age group of 23-27 years in both the groups. The serum calcium level of group A were significantly lower in pre eclampsia women(Group A) in comparison to those of normal pregnancy (control group B ) (8.6 ±1.554 gm/dl Vs 9.893 ± 0.6877 g/dl: p<0.0001).Conclusion: There was a significant reduction in serum calcium levels in pre-eclamptic women as compared to normal pregnant women, suggesting the role of calcium in pre-eclampsia.